The Influence of Musical Activities on Cognitive Control Mechanisms: Overview and empirical findings - Varga, Ágnes; Marton, Klára; Jakab, Zoltán; Láng, Sarolta (Gyermeknevelés Tudományos Folyóirat, 2022)
This article provides an overview of the ways music therapy may contribute to the improvement of cognitive control mechanisms, which play a central role in managing our goal-directed behaviors. First, we introduce the cognitive control model of Cohen (2017) and we summarize the main findings of the literature about the near and far transfer effects of music therapy. The integration of these two theoretical frameworks will allow us to describe the associations between higher-level cognitive control functions and music processing. In the second part of this paper, we present the preliminary findings of our recent study. We examined the relationship between formal regular music training and cognitive control in young adults by focusing on working memory updating and cognitive flexibility. We used the N-back paradigm with manipulations in task complexity and modality (visual (letters and shapes); auditory (pitches and timbres)) to examine whether long-term musical experiences affect working memory updating and cognitive flexibility. Our results revealed that the musicians were more accurate in working memory updating than their non-musician peers. Further, the musicians’ performance was significantly better in the pitch N-back task than in the timbre N-back. In contrast to accuracy, the groups did not differ in reaction time. Our first results support the notion that musical training may promote the development of certain cognitive control skills, but further research is needed to better understand this relationship.